Hubungan Karakteristik Mahasiswa/I Terhadap Tingkat Pengetahuan Pemakaian Lensa Kontak di Stikes Mitra Bunda Persada Batam - Suci Fitriani Sammulia; Desi Maniarti Gusmali; Nana Mardiana (Yayasan Literasi Sains Indonesia, 2023)
Contact lenses are aids that are placed on the surface of the cornea to overcome refractive problems. Contact lenses have been chosen by the public as a substitute for glasses, especially among students without regard to and understanding of the dangers of their use. Currently contact lens users in Indonesia are increasing by more than 15% per year. As the number of wearers increases, contact lens complications also increase. As many as 4-10% of contact lens users experience complications from slight irritation to blindness. This study aims to determine the level of student knowledge of contact lens wear among students of STIKes Mitra Bunda Persada Batam. The method used is descriptive cross sectional study. The use of contact lenses in college students of Mitra Bunda Persada Batam obtained 65 respondents with 31 respondents (48.4%) who were female and medium knowledge were 33 respondents (51.6%), while respondents who were male only 1 person (100%) has moderate knowledge. The results of the data show that the majority of the level of knowledge of STIKes Mitra Bunda Persada Batam students on the use of contact lenses is medium knowledge.